Environmental factors affecting lactation milk yield of Jaffarabadi buffaloes in an organized farm of Gujarat - Dangar, Nikhil; Vataliya, Pravin (Buffalo Bulletin, 2018)
The study was undertaken to evaluate the effect of different macro climatic variables on lactation milk yield of Jaffarabadi buffaloes. Milk data of 158 Jaffarabadi buffaloes with 476 lactation records and the meteorological data over a period of 24 years (1987 to 2010) were obtained from Livestock Research Station, Junagadh Agricultural University, Junagadh, Gujarat, India. The influence of environmental factors on lactation milk yield was non-significant (P>0.05). It was observed that lactation milk yield was highest (1962.53±176.73) among the Jaffarabadi buffaloes calved during winter season as compared to rainy (1674.37±268.49) and summer season (1566.52±108.68). All the climatic variables considered in the study accounted for 4.48%, 32.01% and 29.36% direct variation on lactation milk yield in winter, summer and monsoon season, respectively, as verified by the value of coefficient of determination (R2). This research indicates that Jaffarabadi buffaloes were not much sensitive to seasonal changes on their lactation milk yield. The meteorological observation during the period of study confirmed that there was high value of THI in eight months (March to October) in a year, but it didn’t show any significant effect of lactation milk yield which suggests that most buffaloes are with neutral effects of heat stress or any other macro or micro environmental changes in this region and it suggest this buffalo breed can perform well in round the year. This analysis revealed that this buffalo breed having good genetic potential to perform in any condition.